SAT0096 Window or no window: earlier is better when treating rheumatoid arthritis. (12th June 2018) - van der Pol, J.A.; Bergstra, S.A.; Riyazi, N.; Goekoop-Ruiterman, Y.P.; Chopra, A.; Kerstens, P.; Lems, W.F.; Tsonaka, R.; Huizinga, T.W.; Allaart, C.F.
Abstract : Background: Previous reports on a window of opportunity in rheumatoid arthritis (RA) may be related to the use of slow acting c(onventional) s(ynthetic) DMARDs. We hypothesised that onset of action of therapy might influence whether there is a window of opportunity or whether 'earlier is just better'. Objectives: To investigate the association between symptom duration at treatment onset and the achievement of sustained drug free remission (sDFR) in early RA patients initiating therapy including fast acting prednisone or infliximab, compared to patients initiating csDMARD monotherapy. Methods: We analysed the shape (hyperbolic or linear) of the association between symptom duration and achievement of sDFR (DAS<1.6 and no DMARDs for ≥1 year) for patients initiating combination therapy in 3 cohorts: BeSt, IMPROVED study and METEOR. All patients had arthritis symptoms<2 years. In the BeSt study, early RA patients (1987 criteria) were randomised to 4 targeted treatment strategies: arm 1 and 2 started with csDMARD monotherapy, arm 3 with csDMARDs and tapered high dose prednisone and arm 4 with csDMARD and infliximab. Subsequent treatment adjustments aimed at DAS≤2.4. In the IMPROVED study early RA patients (2010 criteria) were treated with csDMARD and tapered high dose prednisone. Subsequent treatment adjustments aimed at DFR. METEOR is an international observational cohort including daily practice data from patients with a diagnosis and treatment of RA according to the rheumatologist. We selected patients who started on csDMARD monotherapy or a combination of csDMARD with prednisone or anti-TNF and at least 1.5 year follow-up. Missing DAS were imputed using last observation carried forward. We performed Cox regression analyses with as outcome sDFR and as predictor symptom duration and compared the likelihood ratio tests of a linear model and a model with inclusion of natural cubic spline functions (resulting in a hyperbola), to investigate which model was a better fit for the data. Results: In BeSt (n=469), IMPROVED (n=421) and METEOR (n=1653) 54, 110 and 10 patients who started with csDMARD and prednisone or anti-TNF combination therapy, and 53 in BeSt and 15 in METEOR who started with csDMARD monotherapy (no monotherapy in IMPROVED) achieved sDFR. A hyperbolic model did not show a better fit for the data than a linear model (for combination therapy in BeSt p=0.743, IMPROVED p=0.337, METEOR p=0.608, for csDMARD monotherapy in BeSt p=0.609, in METEOR p=0.758). Figure 1 shows the linear association between symptom duration and sDFR per study. These results indicate that the earlier treatment is started, the higher the likelihood of achieving sDFR. However, the data do not suggest that a hyperbolic relationship between treatment onset and outcome sDFR fit the data better. Conclusions: Our data suggest that there is no evidence for a window of opportunity in early RA in 3 cohorts. This was not related to use of fast acting combination therapy including prednisone or anti-TNF instead of slow acting csDMARD monotherapy nor was it dependent on strict treatment to target in a clinical trial. It remains that earlier treatment initiation is better when aiming to achieve sDFR. Disclosure of Interest: J. van der Pol: None declared, S. A. Bergstra: None declared, N. Riyazi: None declared, Y. Goekoop-Ruiterman: None declared, A. Chopra: None declared, P. Kerstens: None declared, W. Lems: None declared, R. Tsonaka: None declared, T. Huizinga Consultant for: UCB, BMS, Pfizer, Roche, Sanofi-Aventis and Boeringher from outside the submitted work., C. Allaart Grant/research support from: The IMPROVED study was designed by the investigators and financially supported during the first year of follow-up by AbbVie. The BeSt study was supported by the Dutch College of Health Insurances, with an additional grant from Schering-Plough BV and Centocor Inc.